A New Reading of Sirach, Prologue 29 - Lee, John A. L. 1942- (2023)
A common interpretation of the difficult word aphomoion in the Prologue to Sirach is as 'copy' or 'exemplar'. The aim of this paper is to question this meaning; to show that there are problems with the text as we have it; and to propose a new reading of the text. If correct, the new reading eliminates a false trail and facilitates a better understanding of the Prologue.
Keywords: aphomoion <griechisch>